Exploratory Factor Analysis of Service Quality Dimensions for Higher Educational Institutes: A Students Perspective (Global Journal of Management and Business Research, 2014)
Abstract not found
Keywords: service quality; I-SERVQUAL model; higher education; HEI2019; s; universities; dimensions; exploratory factor analysis